Molecular mechanism of GPCRs mediating metabolic responses – The role of adrenoceptors in glucose metabolism - Mukaida, Saori (2019)
Insulin-stimulated glucose uptake requires an intricate network of proteins including phosphoinositide 3-kinase, Akt and glucose transporter 4 (GLUT4), and is key to maintaining whole body glucose homeostasis. Dysfunction of insulin action causes diminished glucose uptake/utilization in insulin target tissues. Adrenoceptors (ARs), members of the G protein-coupled receptor superfamily, are also involved in glucose metabolism, and activation of α1A-ARs, β2-ARs and β3-ARs increases glucose uptake in cardiomyocytes, skeletal muscle and brown adipocytes, respectively. However, there is a knowledge gap on the mechanisms involved in AR-mediated glucose uptake, and how they differ from that of insulin, which may be important in disease context (such as type 2 diabetes) where the insulin-signaling pathway is down-regulated.